Mudanças de geração na era digital: o professor de matemática e seus alunos - Gaspari, Jaqueline de (Universidade Federal de São Carlos, 2013)
The society is changing, in this sense, our research arises in order to understand it better, as well as to understand the individuals who compose it. Thus, this research presents a significant relevance, to reflect on the great changes in society that the current technological, information, and digital revolution is causing. And these changes are of interest to us within schools and math classrooms, being often the technological and information area associated with the discipline of mathematics. In writing this dissertation, we present the development paths of research, from choosing a qualitative methodology, which used interviews and questionnaires to the constitution of the research data, until the resulting analyses of dialogue with the chosen theoretical framework, the Mannheim generation theory. Therefore, we intend to answer the research question and the outlined objectives; we also bring along writing, short questions and concerns towards instigating further reflection, as we propose to understand what is laid and not direct solutions. In this context, the guiding question of this research was organized in order to study the Mannheim generation theory, relating it to the social changes brought about by the technological, information, and digital revolution that plaguing the society, trying to understand these changes, especially when it regards to access to the Internet, focusing on the mathematics teacher and their students. Thus, the theoretical framework is centered on two axes; one of them relates to the new technology revolution, in which we address mainly social changes amid the digital age and internet access, as well as, how these changes are happening to our research subjects. The other axis is directly linked to generational issues, from the perspective of the generation theory, written by Karl Mannheim. It was noticed that even with some changes, what still prevails in the math classroom is the traditional teaching, and the informatics and the new technologies have emerged as a new resource for teachers at the planning time; for students, it continues as the entertainment, the search for the news, sometimes in school aid, but mainly to communicate with colleagues and friends. One of the relevant points in studying the Mannheim generational theory is the new way to realize what is a generation, away from the original idea of the chronological focus. We have understood that the speed of changes generated by new technologies leads to generational nuances in contrast to disruptions that marked the another generations in earlier times, i.e., the change of generations does not happen abruptly, but there is a continuous unfolding, where the interaction among the generations is one of the pillars of social evolution. The dissertation results in a novel and interesting theoretical approach, uniting the theme of the digital age, the math teacher and their students, present at some time in academic research, in both areas education and mathematics, with the generational studies of the sociologist Mannheim. With this dialogue, we try to show new possibilities of reflection on the daily math teacher and their students.
Keywords: Educação; Mudanças de gerações; Acesso à Internet; Professores e alunos; Matemática; Novas tecnologias digitais; Professor de matemática e seus alunos; Generation changes; New digital technologies; Access to the internet; Math teacher and his students; CIENCIAS HUMANAS::EDUCACAO